La imagen de América Latina en la revista Cuadernos Hispanoamericanos : 1948-1951 - Virágh, Anna (Acta Hispanica, 2011)
The paper presents the way the independence of the Latin American countries, their relations withSpain and their future perspectives were represented in the first volumes of CuadernosHispanoamericanos, a cultural magazine of propagandistic aims established by the Francoistgovernment in 1948. In the aftermath of the Second World War, the Francoist regime, forced into arelatively extended international isolation by the resolutions of the UN, had to tone down itsinternational propaganda and seek allies for its cause, resulting in a rapprochement towards LatinAmerican countries. Cuadernos Hispanoamericanos was a more sophisticated means of thispropaganda, although it also had the important merit of encouraging a real dialogue between LatinAmerican and Spanish intellectuals and artists. The authors of the magazine retained the principalcharacteristics of the official ideology of Hispanidad, but also argued for a more balanced relationshipbetween Latin America and Spain, and saw Latin America as an emerging power within theinternational sphere.